PENGARUH GAME ONLINE TERHADAP PRESTASI BELAJAR DAN MOTIVASI BELAJAR SISWA MI MIFTAHUL HUDA SENDANG TULUNGAGUNG - Nik Haryanti; Mar’atul Hasanah; Setyaning Utami (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The development of technology in the current digital era is very fast and rapid. Various technological advances can be obtained easily. Along with the times and the rapid development of technology, information and communication between humans can be done with various tools or facilities, one of which is a means for refreshment, such as playing online games.